Implementation of Total Quality Management in Waqf Management at the Al-Qur'an Waqf Board Yogyakarta - Indra Sholeh Husni; Arizqiya Nurfattah; Meichio Lesmana; Ahmad Iqbal (Proceedings of Femfest International Conference on Economics, Management, and Business, 2024)
The development of the waqf paradigm in society represents a significant momentum in the effort to transform waqf management from traditional to professional practices, aiming to enhance the function and usefulness of waqf. To achieve this, waqf needs to be managed and developed professionally while adhering to Islamic Shari'a principles. However, many institutions or Nazir still do not manage waqf funds professionally. This research specifically discusses the implementation of Total Quality Management (TQM) and its application in the management of waqf at the Al-Qur'an Waqf Board (BWA) Yogyakarta. The main aim of this study is to examine the implementation of TQM in the management of waqf assets at BWA Yogyakarta. This study uses a descriptive qualitative method with a socio-economic approach to analyze the management of waqf in an institution responsible for collecting and distributing waqf funds. The implementation of TQM at BWA Yogyakarta has been carried out effectively, as indicated by the fulfillment of four out of five TQM indicators. However, there is one indicator that has not been fully implemented: the long-term commitment of Nazir. BWA Yogyakarta currently applies an annual contract system for Nazir, without a service period, which means that Nazir can continue to be part of the institution even after the age of 60. This lack of a long-term commitment leads to frequent changes in staff, which could affect the consistency and sustainability of waqf management. Despite this, the overall implementation of TQM at BWA Yogyakarta has been effective in meeting most of the TQM indicators, with the exception of the long-term commitment indicator.